МОДЕЛЮВАННЯ ЕЛЕКТРИЧНОГО ПОЛЯ В ЕЛЕКТРОДНІЙ СИСТЕМІ ЗАДЛЯ СТВОРЕННЯ ІМПУЛЬСНОГО БАР’ЄРНОГО РОЗРЯДУ В АТМОСФЕРНОМУ ПОВІТРІ ЗА ПРИСУТНОСТІ ВОДИ В КРАПЛИННО-ПЛІВКОВОМУ СТАНІ - Берека, В.О.; Божко, І.В.; Бржезицький, В.О.; Гаран, Я.О.; Троценко, Є.А. (Інститут електродинаміки НАН України, Київ, 2020)
By simulation, it was stated the distribution of the electric field strength and potential in electrode sstem for creation a pulsed barrier discharge in atmospheric air in the presence of water in it in a droplet-film state. The calculations were performed under the conditions that the duration of the pulse front is ≈40 ns, the width of the gas gap is 3.2 mm, the thickness of the water films on its walls is 0.15 mm and the diameter of the droplets is 0.5 - 1.5 mm. It is shown that the presence of water droplets dramatically changes the distribution of the field in the gap: from uniform it becomes sharply inhomogeneous. The maximum field strength is observed at points on the surface of the drop, which are located nearest to the walls of the gap. This field strength is ≈2.5 times higher than that characteristic of a uniform field in the absence of a drop. The effect of neighboring drops on the distribution of the electric field is also considered. It becomes significant (> 10%) when the distance between adjacent drops becomes less than ≈1.5 mm. Referenses 8, figures 6.